ANALISIS PENGARUH DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI EFEKTIVITAS IKLAN, BRAND EQUITY (Studi pada Sabun LUX di Area Semarang) - Setyowirasti, Astrini; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2016)
Purchase Decision is an act that begins with the perception of a product and aninterest in buying the product. In this modern era of increasingly fierce competition among products, this is what causes the decline in purchasing decisions due to the effectiveness of advertising and brand equity is less effective at LUX products. This decline marked by the decline in market share. This study aimed to analyze the influence of variables advertising effectiveness, brand equity and buying interest on purchasing decisions and are expected to increase the return rate LUX product purchasing decisions. Methods of data collection were performed using non-probability sampling techniques. Data were collected through questionnaires from multiple data sources responder community in Semarang, using the data  of  192  respondents.  And  the  results  of  data  processing  using  SEM  (Structural Equation Modeling) through AMOS program.The test results from these studies show that the variable attractiveness of advertising has influence positive and significant impact on the advertising effectiveness , the variable advertising effectiveness also has the effect of positive and significant impact on brand equity. And variable advertising effectiveness and brand equity, positive effect on the variable purchase interest, followed by a variable Brand Equity and Purchase Interest also significant and has positive influence in intreasing the purchasing decision.